Effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) Approach in Developing Poetry Writing Skills and Learning Motivation Among Slow Learner Students - Marlena, Marlena; Mumpuniarti, Mumpuniarti (Journal of Innovation and Research in Primary Education, 2025)
Poetry writing instruction remains challenging for slow learner students who experience difficulties in abstract concept comprehension, idea organization, and vocabulary selection. This study examined the effectiveness of the SAVI (Somatic, Auditory, Visual, Intellectual) approach in enhancing poetry writing skills and learning motivation among slow learners in an inclusive elementary classroom. Employing a two-cycle classroom action research design following the Kemmis and McTaggart model, this study involved 15 fifth-grade students, including 12 identified slow learners, at SDN 008 Muara Ancalong. Data were collected through poetry writing assessments, classroom observations, semi-structured interviews, and field notes. Quantitative data were analyzed descriptively to calculate mean scores and completion percentages, while qualitative data underwent thematic analysis. Student mastery increased substantially from 0% at baseline to 27% after Cycle I and 67% after Cycle II, surpassing the 60% success criterion. Mean poetry writing scores improved by 64% from baseline (45.3) to final assessment (74.5). Qualitative findings revealed enhanced student engagement, creative expression, self-confidence, and intrinsic motivation. Students demonstrated improved metaphorical thinking, diction selection, and willingness to share their work publicly. The multisensory SAVI approach effectively addressed slow learners' cognitive and motivational challenges by providing concrete experiential foundations, visual scaffolding, auditory modeling, and intellectual reflection opportunities. These findings validate multisensory instruction as an accessible, effective strategy for inclusive poetry writing pedagogy.